PEMBERDAYAAN MASYARAKAT DENGAN MENINGKATKAN PENGELOLAAN LIMBAH RUMAH TANGGA ORGANIK DAN ANORGANIK DENGAN KONSEP ZERO WASTE DI DESA SENGGIGI - Yusrin, Yusrin; Berliana , Ni Ketut; Reshi, Regina; Putri, Aulia Wulandari; Salsabila, Baiq Sagita; Zulfa, Nizar Gulam; Oktaviani, Bunga; Novitasari, Silvia; Khairunnisa, Nadia; Irmayanti, Siti; Aziz, Khaerul (Jurnal Wicara, 2024)
The UNRAM 2024 KKN-PMD student group focuses on collaborating with the Senggigi Village community in efforts to deal with organic and inorganic waste. Efforts that can be made to handle vegetable waste and plastic waste can be used as compost and various crafts using the ecobrick method. The main aim of this service is to reduce the amount of waste accumulated and develop the local ecosystem by making various crafts using ecobricks and making compost. Apart from that, the aim is to increase awareness among the community and improve environmental cleanliness in Senggigi Village. The approach is implemented through education and practice. From this activity, it was found that the community, especially teenagers, gained awareness of being able to manage waste by recycling waste into useful products.